Safety, Efficacy and Doxorubicin Pharmacokinetics During Cannabidiol/Cannabidiolic Acid Rich Hemp Oil Use in Dogs With Lymphoma Undergoing CHOP Chemotherapy - Amandine Lejeune; Sandra Bechtel; Rowan Milner; Lana Fagman; Francisco A. Leal Yepes; Joseph J. Wakshlag (Journal of Veterinary Internal Medicine)
ABSTRACT Background The safety of oral cannabidiol (CBD) and cannabidiolic acid (CBDA)‐rich hemp oil supplementation in dogs with cancer receiving chemotherapy has not been investigated. Objectives To evaluate the safety, tolerability, and influence on doxorubicin exposure over time of oral CBD/CBDA‐rich hemp oil supplementation in dogs diagnosed with high grade lymphoma undergoing CHOP chemotherapy. Animals Client‐owned dogs diagnosed with lymphoma. Methods Dogs were enrolled in this prospective, double‐blinded, randomized, placebo‐controlled clinical trial to receive either CBD/CBDA‐rich hemp oil capsules or placebo during one cycle of CHOP chemotherapy. Primary outcomes evaluated included adverse events during chemotherapy, quality of life scores and doxorubicin area under the curve (AUC) over a 5‐week period. Results Twenty‐five dogs were enrolled, with 19 completing the trial. CBD/CBDA supplementation did not significantly affect doxorubicin AUC in the intervention group. The doxorubicin AUC was not different between groups at week 0 [placebo 390.8 nM/h (318.6–479.4); CBD/CBDA 403.4 nM/h (351.9–462.5)] but was different at week 5 [placebo 572.6 (448.3–731.2); CBD/CBDA 406.8 (3.23.2–551.8)]. CBD/CBDA supplementation was well‐tolerated, and no serious adverse events were observed. No significant differences between groups were observed in hematological and biochemical variables. The mean (range) quality of life scores for placebo and CBD were 7.56 (0, 35), and 10.75 (0, 56), respectively, with no significant differences. Conclusion and Clinical Importance Short‐term oral CBD/CBDA‐rich hemp supplementation appeared safe and well‐tolerated in dogs undergoing CHOP chemotherapy for lymphoma.